Astilbin prevents bone loss in ovariectomized mice through the inhibition of RANKL‐induced osteoclastogenesis. Issue 12 (11th October 2019) - Jin, Haiming; Wang, Qingqing; Chen, Kai; Xu, Ke; Pan, Hao; Chu, Feifan; Ye, Zhen; Wang, Ziyi; Tickner, Jennifer; Qiu, Heng; Wang, Chao; Kenny, Jacob; et al.
Abstract: Osteoporosis is the most common osteolytic disease characterized by excessive osteoclast formation and resultant bone loss, which afflicts millions of patients around the world. Astilbin, a traditional herb, is known to have anti‐inflammatory, antioxidant and antihepatic properties, but its role in osteoporosis treatment has not yet been confirmed. In our study, astilbin was found to have an inhibitory effect on the RANKL‐induced formation and function of OCs in a dose‐dependent manner without cytotoxicity. These effects were attributed to its ability to suppress the activity of two transcription factors (NFATc1 and c‐Fos) indispensable for osteoclast formation, followed by inhibition of the expression of bone resorption‐related genes and proteins (Acp5/TRAcP, CTSK, V‐ATPase‐d2 and integrin β3). Furthermore, we examined the underlying mechanisms and found that astilbin repressed osteoclastogenesis by blocking Ca 2+ oscillations and the NF‐κB and MAPK pathways. In addition, the therapeutic effect of MA on preventing bone loss in vivo was further confirmed in an ovariectomized mouse model. Therefore, considering its ability to inhibit RANKL‐mediated osteoclastogenesis and the underlying mechanisms, astilbin might be a potential candidate for treating osteolytic bone diseases.